Syrian refugees minors in Turkey. Why and how are they discriminated against and ostracized? - Demir, Selçuk Beşir (My University, 2019)
This qualitative study aims to explore the extent to which 8–15-year-old Syrian children in Turkey face discrimination and ostracism at school and in the community, as well as to reveal what they think about their life in Turkey. The study group was 22 Syrian refugee children, recruited using criteria sampling by taking into account such personal data as age, gender, school attendance and so forth. Semi-structured interviews were used to collect data about their feelings. Two distinct forms of semi-structured interviews were conducted: One for the participants who attend school, and another for those who do not. The data from the semi-structured interviews were analysed using NVivo v10. The results of the study indicate that the participants encountered discrimination and ostracism in public places, such as schools, hospitals, parks and public transport. The participants consistently reported that they faced discriminatory acts such as humiliation and rejection by peers, while also witnessing attitudes of indifference by others. They also reported that they usually witnessed public apathy. Another major problem was that they are often exploited in workplaces (if they are working) and are paid less. The findings globally suggest that they suffer from widespread discrimination and ostracism. Therefore, a significant number of them have reported that they are mostly unhappy with life in Turkey and want to return to their home country.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Syrian refugees; Minors; Discrimination; Ostracism; Turkey